Adaptability, Knowledge, Resilience: Effects on Socialization in a Post COVID-19 Context – Empirical Study - López-Torres, Virginia Guadalupe; Jiménez Terrazas, Carmen Patricia (2024)
Objective: The objective of the study is to analyze the socialization of Covid-19 in university students based on its relationship with knowledge, adaptability and resilience. Theoretical Framework: The theory of socialization analyzes the associations between lived experiences, behaviors, beliefs and dispositions, in particular, socialization focuses on Covid-19 considering that having socialization of information and knowledge helps to overcome challenges, adapt and be resilient when being better prepared for a future contagion or a new pandemic. Method: Quantitative research, empirical, non-experimental, cross-sectional design, sample of university students. Data collection by questionnaire. Data analysis by partial least squares structural equation modeling (PLS-SEM). Results and Discussion: The results confirm that knowledge has a strategic role in triggering adaptability, resilience and successful socialization post Covid-19 and support the theory of socialization, elements that are conducive to chaotic situations such as the pandemic. Research Implications: Professors and university staff, as a socializing organization, can influence formal processes that enhance the social integration of students, acquiring knowledge that allows them to adapt and be resilient to Covid-19 outbreaks or new pandemics. Originality/Value: Innovative study since, according to the review conducted, there are no previous studies that investigate the direct and indirect effect of adaptation, resilience and knowledge on post covid-19 socialization.